Enhanced Effect of NaOH/Thiourea/Urea Aqueous Solution on Paper Strength of High Yield Pulp - Rui Zhai; Xiaofan Zhou (BioResources, 2014)
In this work, the thermomechanical pulp of Pinus massoniana was pretreated with a NaOH/thiourea/urea aqueous solution to promote fiber bonded area and to increase paper strength. The effects of pulp concentration, alkali dosage, dipping time, and freezing time were evaluated through single factor experiments. The optimum conditions were found to be 15% pulp consistency, 8% NaOH, a dipping time of 15 min, and a freezing time of 60 min. Under these conditions, the paper tensile and burst index of treated pulp increased nearly 100%, and the bulk also was reduced by 10%, but there were no significant effects on folding.